1988
DOI: 10.1128/jb.170.10.4897-4902.1988
|View full text |Cite
|
Sign up to set email alerts
|

Induction, isolation, and some properties of the NADPH-dependent glutamate dehydrogenase from the nonheterocystous cyanobacterium Phormidium laminosum

Abstract: The level of the NADPH-dependent glutamate dehydrogenase activity (EC 1.4.1.4) from nitrate-grown cells of the thermophilic non-N2-flxing cyanobacterium Phormidium laminosum OH-1-p.Cl1 could be significantly enhanced by the presence of ammonium or nitrite, as well as by L-methionine-DL-sulfoximine and other sources of organic nitrogen (L-Glu, L-Gln, and methylamine). The enzyme was purified more than 4,400-fold by ultracentrifugation, ion-exchange chromatography, and affinity chromatography, and at 30°C it sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…We obtained K m values of 43.72 mM for ammonium (aminating activity) and 56.45 mM for glutamate (deaminating activity). These results are consistent with previous studies on cyanobacteria (Martínez‐Bilbao et al. , 1988) and if we take into account the reported cyanobacterial pools of ammonium (0.64–2 µM, calculated from Boussiba et al.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We obtained K m values of 43.72 mM for ammonium (aminating activity) and 56.45 mM for glutamate (deaminating activity). These results are consistent with previous studies on cyanobacteria (Martínez‐Bilbao et al. , 1988) and if we take into account the reported cyanobacterial pools of ammonium (0.64–2 µM, calculated from Boussiba et al.…”
Section: Resultssupporting
confidence: 93%
“…We obtained K m values of 43.72 mM for ammonium (aminating activity) and 56.45 mM for glutamate (deaminating activity). These results are consistent with previous studies on cyanobacteria (Martínez-Bilbao et al, 1988) and if we take into account the reported cyanobacterial pools of ammonium (0.64-2 mM, calculated from Boussiba et al, 1984) and glutamate (24.5-182.3 mM; Zahradnícková et al, 2007), they might suggest a catabolic role for NADPH-GDH in Prochlorococcus. Km have also been determined for GDH in other organisms by other teams, and in particular in the cases of Km for ammonium and L-glutamate, there exists a great diversity.…”
Section: Detection and Characterization Of The Aminating And Deaminatsupporting
confidence: 93%
“…One hypothesis to explain this result is that ammonium-assimilating enzymes (GS, GOGAT, and glutamate dehydrogenase GDH) [25], [80], [82]-[84] in corals are stimulated by seawater acidification, possibly through the impact of acidification on the intracellular pH [85]. For example, the activity of GS, GOGAT, and GDH are influenced by pH in an actinobacteria [86] and a cyanobacteria [87], with pH T optima of 7.0 (GS), 7.2-7.6 (GOGAT), and 7.2-7.5 (GDH). In the coral S. pistillata , GDH aminating activity is also pH-dependent, as it increased when pH T was decreased between 8.1 and 7.3 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Wild mycelia grown on ammonium containing medium supplemented with MSX were able to grow normally, indicating that NADP-GDH alone is able to assure ammonium assimilation (Fig, IA), Tbe apparent glutamate-inducible nature of the NADP-GDH (Tab. 1) has been reported for the ascomycete Sphaerostilbe repens , the basidiomycete Coprinus cinereus (Moore 1981) or the cyanobacteritim Phormidium laminosum (Martinez-Bilbao et al, 1988). Opposite results were found in Neurospora crassa (Hernandez et al, 1983) and Candida nitratophila (Hipkin et al 1990) since higher activities were found when organisms were grown on ammonium as nitrogen source than when grown on glutamate.…”
Section: Transfer Experimentsmentioning
confidence: 93%